Physical and sexual abuse in women with functional constipation - Ulus Salih AKARCA; Yüksek Hemşire Nimet TÜZOMAY; Eren AKÇİÇEK; Galip ERSÖZ; Ahmet AYDIN; Ömer ÖZÜTEMİZ; G. SEYLAN (Turkish Journal of Gastroenterology, 2019)
-